KAJIAN EFISIENSI TEKNIS DAN PREFERENSI RISIKO PRODUKSI PETANI DALAM RANGKA PENINGKATAN PRODUKTIVITAS USAHATANI PADI SAWAH DI KABUPATEN BUNGO PROVINSI JAMBI - INDONESIA - nainggolan, saidin; Fitri, Yanuar; Kurniasih, Siti (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
This study aims (1) To find out the description of the allocation of the use of inputs, production and the influence of the use of inputs to the production of lowland rice farming (2) To determine the technical efficiency and productivity function of lowland rice farming (3) To determine the risk preferences of paddy rice production farmers. 4) To find out the model for increasing the productivity of lowland rice farming by taking into account the technical efficiency and risk preferences of farmers. The location of the research was Tanah Sepenggal Subdistrict, Bungo.The location was chosen purposively. The data used were primary data. Primary data include production and output inputs, input and output prices, primary data obtained directly from farmers using a questionnaire. The sample size of 70 farmers. The method of sampling is the Simple Random Sampling Method. The data analysis method uses the Kumbhakar Function Model with the Stochastic Frontier approach. The use of production inputs is still not technically efficient because the average technical efficiency is only 0.6235 (MT I) and 0.5647 (MT II). The behavior of rice farmers is risk averter. The risk averse behavior of farmers has consequences for the allocation of inputs used. The more avoiding the risk of productivity, the less input allocation used, this is evident from the use of production inputs below the recommended dosage so that the productivity achieved by farmers is low. The combination of the use of production inputs will affect the level of technical efficiency. Low average technical efficiency indicates that the risk preferences of lowland rice farmers affect the level of technical efficiency. To produce optimal productivity, it must use optimal production inputs. Key word : Technical Efficiency and Risk